Pengaruh Lingkungan Kerja Fisik Dan Non Fisik Terhadap Kinerja Karyawan Pada PT. Adis Dimension Footwear Wilayah Balaraja Kabupaten Tangerang - Salza Haditsah, Mitha; Darmadi Darmadi (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the influence of physical and non-physical work environments on employee performance at PT. Adis Dimension Footwear, Balaraja District, Tangerang Regency. The approach used in this research is quantitative with an associative method. Data analysis techniques include validity test, reliability test, classical assumption test, regression analysis, coefficient of determination, and hypothesis testing. The population in this study consisted of 70 respondents. The results show that the physical work environment has a positive and significant effect on employee performance, with the regression equation Y = 16.172 + 0.605 X1 and a determination coefficient of 51.4%. The non-physical work environment also has a positive and significant effect, with the regression equation Y = 15.113 + 0.624 X2 and a determination coefficient of 49.2%. Simultaneously, both variables have a positive and significant effect on employee performance, with the regression equation Y = 12.814 + 0.366 X1 + 0.327 X2 and a determination coefficient of 56.9%. The F-test result shows Fcount > Ftable (44.239 > 3.13), and the significance value is < 0.05, thus all alternative hypotheses are accepted. These findings highlight the importance of optimizing both physical and non-physical work environments to enhance overall employee performance